Fabrication of ceramic membrane chromatography for biologics purification - Mel, Maizirwan; Abdeen, Fouad R. H.; Sopyan, Iis (IIUM Press, 2011)
Chromatography is one of the most important separation processes of choice for the recovery/purification of proteins and complex bio-structures. Fabrication of chromatographic membranes and their efficiency in the chromatography process has been the subject of many recent researches. In this study, a coin-like, 13 mm diameter and 3 mm thick, ceramic membrane was fabricated to be used as a chromatographic medium. The membrane is used to replace the conventional resin-based chromatography columns. Hydroxyapatite (HA) powder was used as a material for the membrane fabrication. In this project, a HA powder was produced using starch as pore creating agents. Characterization processes were done for the ceramic membrane using the suitable apparatuses. Three parameters of the fabrication process (starch wt %, compaction pressure and sintering temperature) were manipulated to optimize the performance of the membrane. The fabricated membrane was placed in a (FPLC) system to be tested for its performance as an adsorptive membrane. (IMAC) process was run by immobilizing Ni2+ ions at the membrane particles surfaces. NP protein of the (NDV) was used to test the membrane’s ability to bind Histidine-tagged proteins. The optimum set of process parameters that yielded in the highest porosity and good chromatogram was determined to be 5 wt % starch, 3000 psi compaction pressure and 1100°C sintering temperature.